Post-harvest evaluation of Arabica and Robusta coffee for physical, mechanical and aerodynamic properties - Channabasamma, B.B.; Sandeep, T.N.; Gopinandhan, T.N.; Nagaraja, J.S. (Journal of Plantation Crops, 2022)
Knowledge about physicomechanical and aerodynamic properties is indispensable for any crop that undergoes post-harvest processing; coffee is no exception. These properties are the most crucial parameters for designing and developing processing machinery and storage structure. As far as coffee is concerned, these properties are imperative for designing dryers, hullers, peeler-cum-polisher and size graders. Though coffee is one of the leading plantation crops in India, published reports on physical, mechanical and aerodynamic properties are rather limited. In this direction, a study was attempted to generate data in respect of physical (length, width, thickness, volume, surface area, thousand seed weight, bulk density, true density and porosity), mechanical (angle of repose and co-efficient of friction) and aerodynamic (terminal velocity) property in different coffee types (parchment, cherry and clean coffees of both Arabica and Robusta varieties). At the prescribed moisture content of 11 per cent, the length, width, thickness, volume and surface area were significantly higher (p=0.05) in cherry coffee, followed by parchment and clean coffees. The porosity, bulk density and true density were found in the order of 45 to 58 per cent, 395 to 466 kg m-3 and 856 to 944 kg m-3 for cherry, 56 to 57 per cent, 400 to 410 kg m-3, 950 to 966 kg m-3 for parchment and 37.5 to 44 per cent, 691 to 780 kg m-3 and 1,106 to 1,401 kg m-3 for clean coffee, respectively. There were no significant differences between coffee types in respect of angle of repose, co-efficient of friction and terminal velocity. The data generated under this study can be harnessed while configuring or improving the coffee processing machinery and helps achieve the final product with desirable quality characteristics.